2017
DOI: 10.1128/microbiolspec.funk-0040-2016
|View full text |Cite
|
Sign up to set email alerts
|

Thigmo Responses: The Fungal Sense of Touch

Abstract: The growth and development of most fungi take place on a two-dimensional surface or within a three-dimensional matrix. The fungal sense of touch is therefore critical for fungi in the interpretation of their environment and often signals the switch to a new developmental state. Contact sensing, or thigmo-based responses, include thigmo differentiation, such as the induction of invasion structures by plant pathogens in response to topography; thigmonasty, where contact with a motile prey rapidly triggers its ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 149 publications
0
17
0
Order By: Relevance
“…These results suggest that dermatophytes are able to degrade intercellular junctions (e.g., corneodesmosomes or tight junctions) and/or the extracellular lipid matrix. In addition, these observations also suggest that hyphal elongation is orientated according to the physical and topographical features of the substrate in order to facilitate its invasion, a phenomenon known as "thigmotropism" [76]. This ability of dermatophytes to orientate their growth was also described by Perera et al [77] who observed the growth of Epidermophyton floccosum, M. canis, and T. mentagrophytes on artificial membranes.…”
Section: Germination and Invasion Of The Host Tissuementioning
confidence: 60%
“…These results suggest that dermatophytes are able to degrade intercellular junctions (e.g., corneodesmosomes or tight junctions) and/or the extracellular lipid matrix. In addition, these observations also suggest that hyphal elongation is orientated according to the physical and topographical features of the substrate in order to facilitate its invasion, a phenomenon known as "thigmotropism" [76]. This ability of dermatophytes to orientate their growth was also described by Perera et al [77] who observed the growth of Epidermophyton floccosum, M. canis, and T. mentagrophytes on artificial membranes.…”
Section: Germination and Invasion Of The Host Tissuementioning
confidence: 60%
“…This suggests that the inhibition of the AF biosynthesis does not depend directly on the actual inoculated ratio of the two strains. It still has to be clarified in further experiments whether this inhibition acts on levels beyond the thigmotropic or competitive exclusion principles (Cotty and Bayman 1993 ; Almeida and Brand 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms are competition for nutrients and competitive exclusion, which is a thigmo-based response (Cotty and Bayman 1993 ; Huang et al 2011 ). Thigmo-based responses are mediated by direct contact between the fungal cells and the environment (Almeida and Brand 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adapting growth to penetrate substrates is related to two sensorresponse systems: chemotropism (Turrà et al, 2016) and thigmotropism (Almeida and Brand, 2017). The biochemical mechanisms underlying chemo-and mechano-sensing are very diverse, and generally result in activation of MAP kinase and cAMP signaling cascades (Turrà et al, 2016;Braunsdorf et al, 2016).…”
Section: Penetration (Invasive Growth)mentioning
confidence: 99%